An integrated multicomponent care model for men affected by prostate cancer: A feasibility study of TrueNTH Australia. Issue 9 (24th May 2021) - Yates, Patsy; Carter, Rob; Cockerell, Robyn; Cowan, Donna; Dixon, Cyril; Magnus, Anne; Newton, Robert U.; Hart, Nicolas H.; Galvão, Daniel A.; Baguley, Brenton; Denniston, Nicholas; Skinner, Tina; et al.
Abstract: Objective: To evaluate the feasibility of implementing an integrated multicomponent survivorship care model for men affected by prostate cancer. Methods: Using a single arm prospective cohort study design, men with prostate cancer were recruited from two regional public hospitals in Australia for a 6‐months program that provided information and decision support, exercise and nutrition management, specialised clinical support, and practical support through localised and central care coordination. Carers of the men were also invited to the program. Data were collected from multiple sources to evaluate: (1) recruitment capability and participant characteristics; (2) appropriateness and feasibility of delivering the specific intervention components using an electronic care management tool; and (3) suitability of data collection procedures and proposed outcome measures. Results: Of the 105 eligible men, 51 (consent rate 49%) participated in the program. Of the 31 carers nominated by the men, 13 consented (consent rate 42%). All carers and 50 (98%) men completed the program. Most (92%) men were newly diagnosed with localised prostate cancer. All men attended initial screening and assessment for supportive care needs; a total of 838 episodes of contact/consultation were made by the intervention team either in person (9%) or remotely (91%). The intervention was implemented as proposed with no adverse events. The proposed outcome measures and evaluation procedures were found to be appropriate. Conclusions: Our results support the feasibility of implementing this integrated multicomponent care model for men affected by prostate cancer.